Characteristics of unemployment dynamics: The chain reaction approach - Marika Karanassou; Dennis J. Snower (Institute for the Study of Labor (IZA), 2000)
The aim of this paper is to analyze and estimate salient characteristics of unemployment dynamics. Movements in unemployment are viewed as "chain reactions" of responses to labor market shocks, working their way through systems of interacting lagged adjustment processes. In the context of estimated labor market systems for Germany, the UK, and the US, we construct aggregate measures of unemployment responses to temporary and permanent shocks. These measures are temporal (depicting how long it takes for unemployment to reach long-run equilibrium) and quantitative (depicting the cumulative amount of unused labor resources generated in the aftermath of a shock). Furthermore, we estimate the contributions of individual lagged adjustments to these aggregate measures. Our empirical results indicate that (i) lagged adjustment processes play an important part in explaining how temporary and permanent shocks affect unemployment, (ii) temporary and permanent shocks can yield quite different inter-country comparisons of unemployment effects, and (iii) the quantitative and temporal measures can also yield markedly different inter-country comparisons. This analysis provides insights into the driving forces underlying the movements of unemployment in the countries above.
Keywords: J32; E37; E30; J64; J60; 330; Natural rate hypothesis; Labor markets; Employment; Adjustment costs; Unemployment; Arbeitslosigkeit; Hysteresis; Schock; Arbeitsmarkt; Wirtschaftliche Anpassung; Anpassungskosten; Schätzung; Vergleich; Deutschland; Großbritannien; USA